Effects of a priming session with heavy sled pushes on neuromuscular performance and perceived recovery in soccer players: A crossover design study during competitive microcycles - Pino-Mulero, V.; Soriano, M. A.; Giuliano, F.; González-García, J. (Biology of Sport, 2025)
This study compared the effects of a sled push priming session on performance in 20 m sprint times, vertical jump, and perceived recovery, in comparison to a control condition, during competitive microcycles. Sixteen young semi-professional football players completed two conditions: priming (heavy sled pushes and MD-1 training) and control (only MD-1 regular training), in a crossover design. Twenty-metre sprint times and countermovement jump (CMJ) were assessed 24 hours following the completion of the experimental sessions. The distribution of training load (TL) was similar between the two microcycles on each training day (p > 0.506). At 24 hours, 20 m sprint times were lower (p < 0.001; ES = -1.41), and jump height increased (p = 0.001; ES = 1.11) in the priming condition compared to the control. Individual response analysis showed that 62.5% of the participants ran faster, and 81.3% jumped higher 24 h after priming compared to the control. Furthermore, the added sled push priming exercise did not alter the recovery values perceived by players at 24 hours (p = 0.310). These findings support the use of priming exercises within competitive microcycles by incorporating these sessions on MD-1, as they appear to improve 20 m sprint time and vertical jump without impacting perceived recovery. These results contribute to the understanding of the effects of a low-volume priming session based on heavy sled push on delayed potentiation in sprint and CMJ.